Synthesis of NiO/Y2O3/ZrO2 Catalysts Prepared by One-Step Polymerization Method and Their Use in the Syngas Production from Methane - Yvan J. O. Asencios; Elisabete M. Assaf (International Journal of Chemical Engineering)
In this work, the production of Syngas (H2/CO) from oxidative reforming of methane (ORM) and partial oxidation of methane (POM) over NiO/Y2O3/ZrO2 catalysts was studied. The nickel concentration was varied (ranging from 0 to 40 wt.%) aiming to optimize the performance in ORM and POM reactions; these reactions were carried out at 750°C and 1 atm for 6 hours. The catalysts were prepared by the one-step polymerization method (OSP) and characterized by different techniques. This method led to production of materials of smaller crystallite size than others of similar composition prepared under other methods; the catalysts presented good nickel dispersion, well-defined crystalline structure, and well-defined geometrical morphology. Additionally, the OSP method was advantageous because it was carried out in a single calcination step. The catalyst containing 20% wt. of nickel (20Ni20YZ sample) showed the highest methane conversion, high selectivity to H2 and CO, low carbon deposition rates, and, curiously, the best geometric morphology. The results of this paper also demonstrated that the nickel concentration in the mixture strongly influenced the morphology of the catalysts; therefore, the morphology also influenced the catalytic performances during the Syngas production reactions.